AN INFOTAINMENT FRAMING ANALYSIS: CELEBRITY DIVORCE PORTRAYAL IN INDONESIA - Lambok Hermanto Sihombing; Angella Tiara Gabriella; Ivanna Maria Maria Eveline (The Indonesian Journal of Communication Studies, 2021)
Infotainment has been a part of Indonesian mainstream media segmentation for a long time. Celebrities Divorce cases are one example of a storyline that Infotainment often covers with certain framing to gain more reaction from the public. This study aimed to uncover the framing within  Aura Kasih divorce cases that are being reported by Insert, one  infotainment channel in Indonesia. The researchers used Framing theory by Robert Entman. The dataset was taken from television and social media such as @inserlive, Insert infotainment, Intens Investigasi, and Trans TV Official. The result of this study concluded in several usage of framing that drives people to their own conclusions outside the information that those infotainment offers and proves the effect of said framing to influence the viewers perception and opinion.